DISPOSICIÓN ESPACIAL DE Termes Saltans (WASMANN) (ISÓPTERA: TERMITIDAE: TERMITINAE) - Coronel, Juan M.; Laffont, Enrique R.; Torales, Gladys J.; Porcel, Eduardo (REVISTA DE AGRICULTURA, 2015)
DISPOSICIÓN ESPACIAL DE Termes Saltans (WASMANN) (ISÓPTERA: TERMITIDAE: TERMITINAE)